Research on Business Environment Optimization Paths in Dali County of Weinan City (Journal of Global Humanities and Social Sciences, 2023)
At present, competition in the local economy is becoming increasingly fierce, and the quality of the business environment directly affects a region's investment attractiveness, economic growth rate, and long-term sustainable development. As an important city in Shaanxi Province, Weinan City has been committed to economic transformation and upgrading. Among them, Dali County has gradually emerged due to its unique geographical, cultural, and resource advantages. In recent years, Dali County has achieved certain results in attracting foreign investment, supporting small and medium-sized enterprises, and innovation-driven development. However, to further enhance its competitive position domestically and internationally, it is imperative to continue to optimize its business environment. The article explores the business environment optimization path in Dali County, Weinan City.